ISLAMIC FINANCIAL LITERACY DAN ISLAMIC FINANCIAL BEHAVIOUR MAHASISWA (Studi Etnometodologi Terhadap Efektivitas Pembelajaran Manajemen Keuangan Islam) - Muhammad Fakhri Amir (IQTISHADUNA, 2021)
This study aims to determine whether the learning process of Islamic Financial Management courses has been effective in improving students’ Islamic financial literacy and Islamic financial behaviour. This study is a qualitative research, using an ethnomethodological approach, to be more specific this study employs an Islamic ethnomethodology analysis tool, namely "amiiin". The Islamic ethnomethodology "amiiin" has several stages, they are: deed, knowledge, faith, information revelation and ihsan. Previously, the data were primary data which obtained by observation, interviews, documentation and focus group discussions. The results of this study indicate that Islamic financial management courses are effective in improving students’ Islamic financial literacy and Islamic financial behaviour. Likewise, the "amiiin" ethnomethodology analysis after studying Islamic financial management, their financial management behaviour leads to ihsan behaviour, which is to obtain blessing.